(untitled) (Journal of Partial Differential Equations, 2006)
Professor Jiang Lishang was chief editor of Journal of Partial Differential Equation for 15 years. He made a great effort in the development of this journal. Through the excellent works of him and his colleagues, this journal is playing a more and more important role in the research on partial differential equations in China.